2021
DOI: 10.1186/s40101-021-00258-w
|View full text |Cite
|
Sign up to set email alerts
|

Ambient-task combined lighting to regulate autonomic and psychomotor arousal levels without compromising subjective comfort to lighting

Abstract: Background Although evidence of both beneficial and adverse biological effects of lighting has accumulated, biologically favorable lighting often does not match subjectively comfortable lighting. By controlling the correlated color temperature (CCT) of ambient lights, we investigated the feasibility of combined lighting that meets both biological requirements and subjective comfort. Methods Two types of combined lightings were compared; one consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Considering that cognition, emotion, and alertness may affect visual performance through factors like motivation and preference [39,40], and biologically required lighting characteristics frequently do not match lighting requirements for subjective comfort or for personal activities [41], evaluations in this study will include mental perception (subjective visual fatigue, satisfaction, alertness, emotion), visual performance, and physiological health.…”
Section: Evaluation and Statistical Analysismentioning
confidence: 99%
“…Considering that cognition, emotion, and alertness may affect visual performance through factors like motivation and preference [39,40], and biologically required lighting characteristics frequently do not match lighting requirements for subjective comfort or for personal activities [41], evaluations in this study will include mental perception (subjective visual fatigue, satisfaction, alertness, emotion), visual performance, and physiological health.…”
Section: Evaluation and Statistical Analysismentioning
confidence: 99%
“…In this context, light serves as a crucial modulator of non-visual functions, significantly enhancing alertness and cognitive performance. Studies have shown that specific light treatments, particularly involving flicker, are effective in increasing vigilance and improving overall cognitive task performance by influencing circadian rhythms and neural activity ( Yuda et al, 2017 ; Yan et al, 2018 ; Hayano et al, 2021 ; Nie et al, 2021 ). Despite promising results, comprehensive understanding of the mechanisms through which flicker-induced light influences alertness and interacts with central fatigue remains sparse and warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%